The potency of palm kernel shell as an adsorbent - Kusuma Faisal Muhammad; Widya Dwi Rukmi Putri; Mokhamad Nur (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
The palm kernel shell (PKS) is the endocarp of the oil palm fruit that protects the kernel of the oil palm crops. PKS is a by-product of separating the kernel of the palm kernel nut This by-product tends to be used as a solid biofuel because of it’s high carbon content. Meanwhile, the need for clean water in Indonesia grows year after year. The increased production of clean water is accompanied by the use lot of chemicals as water purification medium. PKS is lignocellulosic biomass with a lot of potential because of its characteristics and contents, including the use of materials as adsorbents. PKS has been evaluated and shown to be useful in dealing with heavy metal pollution. The use of activated carbon-based  PKS as an adsorbent has also been intensively investigated such as using various activation techniques including acid activation and steam activation at high temperatures. There will be variances in their adsorption capability and adsorption process due to differences in structural properties and functional groups, as well as originating from different biomass sources with different varieties.